2014
DOI: 10.1136/bjophthalmol-2013-304711
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced depth imaging optical coherence tomography of the choroid in migraine patients: implications for the association of migraine and glaucoma

Abstract: Choroidal thickness was found to be significantly increased in migraine patients during the attack period when compared to basal levels. The possible implications of this finding on the association between migraine and glaucoma are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…23 In contrast, a different study, similar to our results, reported a decrease in the choroidal thickness in migraine patients, especially five of the patients during attack, according to the control group, which supports our suggestion of decreased blood flow according to the vasogenic theory of migraine. 18 It is also reported that the patients with migraine often suffer from vascular dysregulation involving the choroid 24 and this may be in relation with the choroidal thickness changes in migraine patients.…”
Section: Discussionsupporting
confidence: 91%
“…23 In contrast, a different study, similar to our results, reported a decrease in the choroidal thickness in migraine patients, especially five of the patients during attack, according to the control group, which supports our suggestion of decreased blood flow according to the vasogenic theory of migraine. 18 It is also reported that the patients with migraine often suffer from vascular dysregulation involving the choroid 24 and this may be in relation with the choroidal thickness changes in migraine patients.…”
Section: Discussionsupporting
confidence: 91%
“…They conclude that the increased choroidal thickness of the migraine patients might be due to rebound vasodilatation in the acute attack period. In parallel with these results, Dadaci et al [2] reported choroidal thickening during the attack period in the eyes on the headache side of patients with bilateral or unilateral migraine compared to basal levels. They discussed that presumed neurogenic inflammation can occur in choroid and may result in increased choroidal thickness during a headache attack.…”
Section: Discussionmentioning
confidence: 54%
“…Migraine patients usually have concomitant periorbital pain, photophobia or other visual symptoms [2]. Because ophthalmologists frequently encounter these patients, a detailed ophthalmological examination could provide valuable information about pathogenesis of migraine.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study imaged migraine participants during a migraine attack and reported an increase in choroidal thickness relative to a group of non-headache controls (Karalezli et al, 2014). Dadaci et al (2014) shed further light on this result, by comparing choroidal thickness across two test visits in the same migraine observers (one at baseline, the other during an attack). Choroidal thickness was increased during a migraine attack compared to the baseline interictal visit (Dadaci et al, 2014).…”
Section: Choroidal Imaging In People With Migrainementioning
confidence: 94%